2019
DOI: 10.1111/ap.12384
|View full text |Cite
|
Sign up to set email alerts
|

The psychological distress and physical health of Australian psychology honours students

Abstract: Objective: To measure psychological and physical health of psychology students during their Honours year of study, in the context of this being perceived as a high stake, "make-or-break" degree program in Australia. Method: Psychology honours students from 9 universities (N = 179) completed an online survey that included measures of depression, anxiety and stress, physical activity, drug and alcohol use, self-rated health status, future study intentions and desired final grade for the degree. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Additionally, it can increase aggressive behavior, cause sleep disturbances, and lead to drug addiction and suicidal tendencies (Bebanic et al, 2017;Gyawali et al, Identifying the Risk and Protective Factors of Psychological Distress among Individuals in Asia during the... PSIKOLOGIKA Volume 28 Nomor 1 Januari 2023 2016; Rezaei et al, 2018;Tang et al, 2018). It can also have physiological effects, including obesity, heart disease, and cancer (Almigbal et al, 2019;Jarrad et al, 2019;McLachlan & Gale, 2018). This highlights that psychological distress affects not only mental health but also physical well-being.…”
Section: Sociodemographic Risk Factors Includementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it can increase aggressive behavior, cause sleep disturbances, and lead to drug addiction and suicidal tendencies (Bebanic et al, 2017;Gyawali et al, Identifying the Risk and Protective Factors of Psychological Distress among Individuals in Asia during the... PSIKOLOGIKA Volume 28 Nomor 1 Januari 2023 2016; Rezaei et al, 2018;Tang et al, 2018). It can also have physiological effects, including obesity, heart disease, and cancer (Almigbal et al, 2019;Jarrad et al, 2019;McLachlan & Gale, 2018). This highlights that psychological distress affects not only mental health but also physical well-being.…”
Section: Sociodemographic Risk Factors Includementioning
confidence: 99%
“…Horesh et al, 2020;Lahav, 2020;Shahrour & Dardas, 2020).StudiesAlmigbal et al (2019),Jarrad et al (2019), andMcLachlan andGale (2018) showed that physical health issues can impact psychological well-being. However, during the COVID-19 pandemic, it is not the only factor causing this problem.…”
mentioning
confidence: 99%
“…Author details 1 School of Population Health, The University of New South Wales, Sydney, Australia. 2 School of Liberal Arts and Social Sciences, Independent University, Dhaka, Bangladesh. 3 Department of Sociology, East West University, Dhaka, Bangladesh.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…Psychological distress, especially among the students, has been a major public health concern because it is often associated with reduced academic performance [ 1 ], worse physical health [ 2 ], increased risk of mortality [ 3 ], and elevated healthcare costs [ 4 ]. Existing evidence indicates high prevalence rates of psychological distress among students in low, middle, and high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Stress associated with romantic and family relationships has also been associated with depressive symptoms (Reed, Ferraro, Lucier-Greer, & Barber, 2015; Vrshek-Schallhorn et al, 2015), health (Donnelly, Renk, & McKinney, 2013), and alcohol-related problems in emerging adult samples more broadly (Backer-Fulghum, Patock-Peckham, King, Roufa, & Hagen, 2012). While the amount and impact of this stress may be enhanced during periods of increased importance, such as prior to entry to postgraduate study (Jarrad, Dry, Semmler, Turnbull, & Chur-Hansen, 2019), these stressors are relevant to the emerging adult population as a whole.…”
mentioning
confidence: 99%